Mengungkap Keterkaitan Brand Image dan Cash on Delivery dengan Keputusan Pembelian dan Fungsi Pemediasi Media Sosial - Pudjo Sugito; Anindia Eka Pratiwi; Sunaryati Hardiani (University of Merdeka Malang, 2023)
This study aims to determine the function of social media on the influence of brand image and COD on purchasing decisions of skincare products. This study uses a quantitative descriptive approach. The population of this research is students in Malang City. The sample of this study uses a non-probability technique, namely incidental sampling technique or sampling technique based on chance to interact with researchers and is suitable as a data source. Data collection techniques through questtionnaires that have been tested for validity and reliability. The data analysis used in this research is the Structural Equation Model (SEM) method with the Partial Least Square (PLS) alternative method. The results of this study are that there is a positive and significant effect of brand image on purchasing decisions of skincare products. There is a positive and significant influence of brand image on social media, there is a positive and significant effect of COD on purchasing decisions of skincare products, there is no positive and insignificant effect of COD on the media. Social media, there is a positive and significant influence of social media on purchasing decisions od skincare products, social media is able to mediate brand image on purchasing decisions of skincare products, social media is not able to mediate COD on purchasing decisions of skincare products.